2016
DOI: 10.1111/cei.12774
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous and natural cytotoxicity receptor-mediated cytotoxicity are effector functions of distinct natural killer subsets in hepatitis C virus-infected chimpanzees

Abstract: SummaryIn humans, CD16 and CD56 are used to identify functionally distinct natural killer (NK) subsets. Due to ubiquitous CD56 expression, this marker cannot be used to distinguish between NK cell subsets in chimpanzees. Therefore, functional analysis of distinct NK subsets during hepatitis C virus (HCV) infection has never been performed in these animals. In the present study an alternative strategy was used to identify four distinct NK subsets on the basis of the expression of CD16 and CD94. The expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…NKG2D and NKp46 were the most expressed NKRs in naive animals with medians of 7 and 4% on total lymphocytes, respectively. Low to no expression of NKG2A and NKp30 was observed, similar to other reports (36,38). CD8α, previously used as one of the primary markers for NK cell definition in chimpanzees (31), was expressed on up to 8% of the total lymphocytes, but was more variable and can be also expressed on dendritic cells and B cells in primates.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…NKG2D and NKp46 were the most expressed NKRs in naive animals with medians of 7 and 4% on total lymphocytes, respectively. Low to no expression of NKG2A and NKp30 was observed, similar to other reports (36,38). CD8α, previously used as one of the primary markers for NK cell definition in chimpanzees (31), was expressed on up to 8% of the total lymphocytes, but was more variable and can be also expressed on dendritic cells and B cells in primates.…”
Section: Resultssupporting
confidence: 88%
“…However, ethical concerns and limited availability of these great apes have now abbreviated their use in biomedical research, but non-invasive or retrospective studies can still provide important insights into the evolution of the immune system. Previous studies (31,(36)(37)(38) identified NK cells in chimpanzees on the basis of CD56 and CD16 gating (used in humans) or CD8α and CD16 (used in Old World monkeys) and even more recently CD16 and CD94 on CD3cells. However, these definitions have often been marred by bias and inadvertently included non-NK cells or excluded minor NK cell subpopulations (39).…”
Section: Introductionmentioning
confidence: 99%